Detention empire : Reagan's war on immigrants and the seeds of resistance - Shull, Kristina (Justice, power, and politics., 2022)
"The early 1980s marked a critical turning point for the rise of modern mass incarceration in the United States. The Mariel Cuban migration of 1980, alongside increasing arrivals of Haitian and Central American asylum-seekers, galvanized new modes of covert warfare in the Reagan administration's globalized War on Drugs. Using newly available government documents, Shull demonstrates how migrant detention operates as a form of counterinsurgency at the intersections of U.S. war-making and domestic carceral trends. As the Reagan administration developed retaliatory enforcement measures to target a racialized specter of mass migration, it laid the foundations of new forms of carceral and imperial expansion"--